2005
DOI: 10.1073/pnas.0500073102
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive deficit associated with cholinergic and nerve growth factor down-regulation in experimental allergic encephalomyelitis in rats

Abstract: Clinical symptoms in multiple sclerosis include cognitive dysfunction. Difficulties in learning and remembering new information represent the most common cognitive deficit and are associated with a general and progressive brain pathology. Possible pathogenetic mechanisms for neuronal damage such as neuroprotective strategies are under active investigation also in experimental allergic encephalomyelitis, the most widely used experimental model for multiple sclerosis. In this paper we demonstrate that a selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
52
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 59 publications
4
52
0
Order By: Relevance
“…Postmortem hippocampal analysis of the mice in this study [143] shown that the complete lack of TNF-α due to genetic modification results in cognitive impairment [31]. This is possibly due to the influence that TNF-α exerts on NGF and BDNF.…”
Section: Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…Postmortem hippocampal analysis of the mice in this study [143] shown that the complete lack of TNF-α due to genetic modification results in cognitive impairment [31]. This is possibly due to the influence that TNF-α exerts on NGF and BDNF.…”
Section: Modelmentioning
confidence: 98%
“…In EAE learning and memory is impaired [143]. Postmortem hippocampal analysis of the mice in this study [143] shown that the complete lack of TNF-α due to genetic modification results in cognitive impairment [31].…”
Section: Modelmentioning
confidence: 99%
“…For example, high levels of glutamate produced by activated immune cells and the agonist to 5-hydroxytryptamine receptors are associated with enhanced neuron death, damage to myelin-producing cells, and the development of EAE (15,16). In contrast, acetylcholine degradation inhibition and cannabinoid or vasoactive intestinal peptide administration ameliorate MS/EAE development (13)(14)17).…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 99%
“…Previous studies have demonstrated that manipulating the expression of neurotransmitters and their transporters or receptors can affect the development of MS/EAE (12)(13)(14)(15)(16)(17). For example, high levels of glutamate produced by activated immune cells and the agonist to 5-hydroxytryptamine receptors are associated with enhanced neuron death, damage to myelin-producing cells, and the development of EAE (15,16).…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 99%
“…ChAT protein levels were not affected by GAL in other brain regions, whereas ChAT immunoreactivity was increased in the CA3 hippocampal region of the aged subjects administered the higher dose of DON. Interestingly, DONrelated increases in ChAT activity have also been reported in cultured rat septal cholinergic neurons, and furthermore, DON restored water maze performance, ChAT activity, and NGF mRNA expression in experimental allergic encephalomyelitis in rats (D'Intino et al, 2005). Finally, neither DON nor GAL had significant effects on VAChT or phospho-TrkA levels, whereas both drugs were associated with decreases in both TrkA and p75 NTR in the prefrontal cortex.…”
mentioning
confidence: 96%